2023
DOI: 10.3390/children10010172
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Clinical Symptoms and Biochemical Parameters in Odontogenic Cellulitis of the Head and Neck Region in Children

Abstract: Many cases of cellulitis in the head and neck region among hospitalized pediatric patients are related to odontogenic infections. C-reactive protein (CRP), white blood cell (WBC) count, neutrophils to lymphocytes ratio (NLR), D-dimer, and prealbumin can be used to assess the severity of odontogenic inflammation. The aim of the study is to evaluate the biochemical parameters as a predictor factor of the severity of odontogenic cellulitis in children. This study was conducted from 2020 to 2021 on patients admitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Pericoronitis can be complicated by acute cellulitis threatening the oropharyngeal junction and the freedom of the airways. The teeth of the anterior sectors are also affected, which can result in the following conditions: upper genital cellulitis circumscribed in canine palatal inclusions following untreated or poorly treated peri-coronary disease, thrombophlebitis of the facial vein which leads to thrombosis of the cavernous sinus, maxillary sinusitis in the event of an impaction, high ectopy or in the maxillary sinus, osteitis, and eye disorders [11,[13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Pericoronitis can be complicated by acute cellulitis threatening the oropharyngeal junction and the freedom of the airways. The teeth of the anterior sectors are also affected, which can result in the following conditions: upper genital cellulitis circumscribed in canine palatal inclusions following untreated or poorly treated peri-coronary disease, thrombophlebitis of the facial vein which leads to thrombosis of the cavernous sinus, maxillary sinusitis in the event of an impaction, high ectopy or in the maxillary sinus, osteitis, and eye disorders [11,[13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Donn et al in their study confirmed the presence of elevated CRP and WBC in all types of odontogenic abscesses [ 16 ]. In a previous analysis we assessed a statistically significant positive relationship between CRP and extraoral swelling as well as the NLR correlates significantly with extraoral swelling and the length of hospitalization [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…In the control group, teeth with uncomplicated caries were determined. 1 Parents and older children have explained the purpose of saliva collection.…”
Section: Clinical Examination and Treatmentmentioning
confidence: 99%
“…This condition often results from untreated dental caries, abscesses, or periodontal disease. 1,2 Immediate dental and medical attention is crucial to prevent the infection from spreading and causing more serious health complications. 3 Anatomical differences that significantly impact the course of inflammatory processes in the facial tissues of the skull in children are associated with a lower degree of jaw bone calcification, the presence of wide marrow spaces with a well-developed vascular system, the presence of tooth buds, as well as the existence of a slit-like, undeveloped maxillary sinus and a greater amount of cancellous bone.…”
mentioning
confidence: 99%